2015
DOI: 10.1016/j.bbadis.2015.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia associated skeletal muscle weakness involves mitochondrial dysfunction and epigenetic modifications

Abstract: HHcy has been implicated in elderly frailty, but the underlying mechanisms are poorly understood. Using C57 and CBS+/- mice and C2C12 cell line, we investigated mechanisms behind HHcy induced skeletal muscle weakness and fatigability. Possible alterations in metabolic capacity (levels of LDH, CS, MM-CK and COX-IV), in structural proteins (levels of dystrophin) and in mitochondrial function (ATP production) were examined. An exercise regimen was employed to reverse HHcy induced changes. CBS+/- mice exhibited mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(83 citation statements)
references
References 50 publications
(67 reference statements)
6
75
0
Order By: Relevance
“…These findings together strengthen the current finding that HHcy-associated sarcopenia could be due to compromised regenerative potential and may not be due to excessive muscle atrophy (through activation of atrogin and MuRF) or cell death. However, the previous study also indicated that there was significant reduction in the muscle fiber size in the CBSϪ/ϩ mouse muscles as evidenced by the presence of relatively more intermediate-size muscle fibers instead of large-size muscle fibers (26). The overall reduction in muscle mass and muscle fiber size could be due to other types of atrophy independent of FOXO transcription as well as defective satellite function as described in the current report.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…These findings together strengthen the current finding that HHcy-associated sarcopenia could be due to compromised regenerative potential and may not be due to excessive muscle atrophy (through activation of atrogin and MuRF) or cell death. However, the previous study also indicated that there was significant reduction in the muscle fiber size in the CBSϪ/ϩ mouse muscles as evidenced by the presence of relatively more intermediate-size muscle fibers instead of large-size muscle fibers (26). The overall reduction in muscle mass and muscle fiber size could be due to other types of atrophy independent of FOXO transcription as well as defective satellite function as described in the current report.…”
Section: Discussionsupporting
confidence: 60%
“…However, our previous study ruled out the induction of atrophic genes such as atrogin-1 and MuRF-1 in the intact muscles from CBSϪ/ϩ mice (23). Furthermore, histological sections from CBSϪ/ϩ mice neither exhibited abnormal cellular infiltration nor showed centronuclear muscle fibers that are suggestive of cell death or inflammation (26). These findings together strengthen the current finding that HHcy-associated sarcopenia could be due to compromised regenerative potential and may not be due to excessive muscle atrophy (through activation of atrogin and MuRF) or cell death.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations